Early detection of childhood obesity through extended routine growth monitoring of children below two years of age in the Asia Pacific region. - Leilani Muhardi; Leilani Muhardi; Eline M van der Beek; Marieke Abrahamse-Berkeveld; Hamid Jan b. Jan Mohamed; Ngee Lek; Wendy oddy; V P Wickramasinghe (World Nutrition Journal, 2018)
Introduction Increased body fat deposition during early life predisposes to higher obesity and metabolic disorder risks in later life. This is particularly relevant in the Asia Pacific region where historically prevalent under-nutrition is now been paralleled or even overruled by over-nutrition over the last few decades. This overview aims to evaluate the potential of early detection of obesity (risk) among experts through addition of specific growth monitoring assessments in children during the first two years of life. Methods A discussion among experts from Malaysia, Singapore, Sri Lanka and Australia on infant growth and a qualitative evaluation of current practice highlighted the need to measure body composition to assess the quality of growth. Current tools are mainly directed towards simple anthropometric measures such as body weight, length and head circumference which do not adequately reflect concurrent changes in body composition to detect early life adiposity development. Recent findings have shown benefits of measurement such as the sum of four skinfold thickness (S4SFT) during the first two years of life for risk assessment of later overweight/obesity. We recommend this assessment for routine practice as a proxy for fat deposition in young children. Further studies to understand implementation hurdles and cost-effectiveness of S4SFT and health outcomes in young children in the Asia Pacific region are necessary. Conclusion Inclusion of four skinfold thickness measurements as part of routine growth monitoring assessment, in addition to weight and height, could be recommended to assess adiposity development in early life allowing identification of infants at risk for obesity.